2016
DOI: 10.1111/lam.12624
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and accurate identification of Xanthomonas citri subspecies citri by fluorescence in situ hybridization

Abstract: Xanthomonas citri subsp. citri (Xcc) is an aggressive and hardy pathogen of citrus plants worldwide. Outbreaks are difficult and costly to contain and the establishment of citrus canker results in restricted trade. In order to extend the existing toolkit for identification of Xcc we developed a novel diagnostic approach based on fluorescence in situ hybridization. Our approach is of comparable specificity and sensitivity to existing methods but can be performed directly on infected tissue making it significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Some studies have already demonstrated the potential of molecular diagnosis for Xanthomonas , more specifically for XccA strains, based on several techniques such as conventional PCR, multiplex PCR, real-time PCR (qPCR), nested-PCR, loop-mediated isothermal amplification (LAMP-PCR), droplet digital polymerase chain reaction (ddPCR), BOX-PCR, and FISH (Coletta-Filho et al, 2006; Mavrodieva, Levy & Gabriel, 2004; Munhoz et al, 2011; Ngoc et al, 2009; Park et al, 2006; Rigano et al, 2010; Waite et al, 2016; Zhao et al, 2016; Golmohammadi et al, 2007; Hartung, Daniel & Pruvost, 1993; Kositcharoenkul, Chatchawankanphanich & Bhunchoth, 2011; Cubero & Graham, 2001; Cubero & Graham, 2002; Cubero & Graham, 2005). The wide variety of techniques used in the molecular diagnostics developed for citrus canker solved the problem of cost and low sensitivity presented by serological methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have already demonstrated the potential of molecular diagnosis for Xanthomonas , more specifically for XccA strains, based on several techniques such as conventional PCR, multiplex PCR, real-time PCR (qPCR), nested-PCR, loop-mediated isothermal amplification (LAMP-PCR), droplet digital polymerase chain reaction (ddPCR), BOX-PCR, and FISH (Coletta-Filho et al, 2006; Mavrodieva, Levy & Gabriel, 2004; Munhoz et al, 2011; Ngoc et al, 2009; Park et al, 2006; Rigano et al, 2010; Waite et al, 2016; Zhao et al, 2016; Golmohammadi et al, 2007; Hartung, Daniel & Pruvost, 1993; Kositcharoenkul, Chatchawankanphanich & Bhunchoth, 2011; Cubero & Graham, 2001; Cubero & Graham, 2002; Cubero & Graham, 2005). The wide variety of techniques used in the molecular diagnostics developed for citrus canker solved the problem of cost and low sensitivity presented by serological methods.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnosis is a cost-effective option for identifying pathogens with great genetic proximity. Molecular biology techniques have been extensively used for identifying various species of the genus Xanthomonas (Adikini et al, 2011; Coletta-Filho et al, 2006; Mavrodieva, Levy & Gabriel, 2004; Munhoz et al, 2011; Ngoc et al, 2009; Park et al, 2006; Rigano et al, 2010; Trindade et al, 2007; Waite et al, 2016; Zhao et al, 2016). The genetic diversity of the Xanthomonas pathotypes that infect citus makes their correct identification a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already demonstrated the potential of molecular diagnosis for Xanthomonas, more specifically for XccA strains, based on several techniques such as conventional PCR, multiplex PCR, real-time PCR (qPCR), nested-PCR, loop-mediated isothermal amplification (LAMP-PCR), droplet digital polymerase chain reaction (ddPCR), BOX-PCR, and FISH [22][23][24][25][26][27]29,30,[48][49][50][51][52][53]. The wide variety of techniques used in the molecular diagnostics developed for citrus canker solved the problem of cost and low sensitivity presented by serological methods.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular diagnosis is a cost-effective option for identifying pathogens with great genetic proximity. Molecular biology techniques have been extensively used for identifying various species of the genus Xanthomonas [21][22][23][24][25][26][27][28][29][30]. The genetic diversity of the Xanthomonas pathotypes that infect citus makes their correct identification a challenging task.…”
Section: Introductionmentioning
confidence: 99%